Fortifikasi dari Kedelai (Glicine max L Merr) pada Formula Tortilla Jagung - Karneta, Railia; Kahfi, A.N.; Aluyah, Cik (Seminar Nasional Lahan Suboptimal, 2018)
Karneta et al, 2019. Fortification of  Soybean (Glicine max L Merr) on Corn Tortilla Formula. pp. 465-472. Tortillas are chips with corn ingredients round shape flat with a certain thickness according to taste.  To increase the nutritional value of tortillas, it is necessary to fortify the nuts ingredients, in this study using soybeans. Fortification with soybean based ingredients, in the form of adding tofu flour, tempeh flour or soy flour.  This study aimed to find the type of material and the amount of fortification material from soybeans in order to diversify tortilla processed products to improve the quality and acceptance of consumers.  This study uses a randomized block design which is arranged factorially which consists of 2 factors and repeated 3 times.  The first factor is fortification ingredients, namely tofu flour, tempeh flour and soy flour, and factor II is the amount of fortification material which is 10%, 20% and 30%.  The results of the study are the best treatment because it meets the quality standards of chips was fortified from soybean flour produced tortillas with 2.51% moisture content, 30.29% protein content, 5.24% ash ash and 1.77% fiber content. The amount of fortification material up to 30% still meets the quality standards of chips.  Organoleptic test results that the panelists liked all corn tortillas with fortification from soy based ingredients.  The amount of fortification material is up to 30%, the panelists still like corn tortillas.